THE INFLUENCE OF INFLATION ON THE UNEMPLOYMENT RATE OPEN IN MEDICAL FIELD OF UNITED STATES IN 2018 - Richard Frimpong Oppong; Weihuan Zhou (PT. Radja Intercontinental Publishing, 2021)
This study aims to find out how the effect of inflation on the open unemployment rate in Medical Field Of United States. The research method used is the method of qualitative data and quantitative data. While the data used is secondary data. The method of data analysis in this study uses simple linear regression analysis to obtain a comprehensive picture of the effect of inflation on the open unemployment rate using the SPSS 25 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used. The results of testing the hypothesis using simple regression analysis and t-test show that: that the t-table value of the Inflation variable is 0.992 < the t-table value (df:α :